Pengembangan Instrumen Penilaian Pemahaman Konsep Business Model Canvas pada Mata Kuliah Kewirausahaan - Yayuk Chayatun Machsunah; Ratna Nurdiana; Sutarum Sutarum (JURNAL PENDIDIKAN DAN KEWIRAUSAHAAN, 2023)
Business Model Canvas (BMC) is a business model that must be mastered by students in entrepreneurship courses as an initial provision to plunge into the world of entrepreneurship. This research will produce an assessment instrument to measure students' conceptual understanding in BMC material which consists of 9 assessment aspects, namely Customer Segment, Value proposition, Customer Relationship, Channel, Revenue Stream, Key Resource, Key activities, Key Partnership, and Cost Structure. The assessment instrument was developed using the ADDIE model (Analysis, Design, Development, Implementation and Evaluations). Content validity was carried out by an expert validator and a value of 93.75% was obtained, which means it is very valid. While the results of statistical analysis obtained a correlation value of more than 0.30. This means that all aspects of the assessment are declared valid. The Cronbach's Alpha reliability value was obtained at 0.886, meaning that the instrument has very strong abilities in research measurement tools, so it can be concluded that the BMC conceptual understanding assessment instrument is valid and feasible to use in business model material for entrepreneurship courses.